1998
DOI: 10.2307/3434149
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Synergy by Mixtures of Weakly Estrogenic Hydroxylated Polychlorinated Biphenyls and Pesticides

Abstract: We examined the estrogenicity of binary mixtures of the hydroxylated polychlorinated biphenyls (OHPCBs) 2,4,6-trichloro-4'-biphenylol (2,4,6-TCB-4'-OH) and 2,3,4,5,-tetrachloro-4'-biphenylol and the pesticides endosulfan and dieldrin. The OHPCBs and pesticides were tested in both the MCF-7 focus assay and a competitive estrogen-receptor binding assay. Although the individual OHPCBs were estrogenic in both assays, there was no synergy when they were combined at various concentrations as equimolar mixtures. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…Although the individual OH-PCBs were estrogenic in both assays, there was no synergy when they were combined at various concentrations as equimolar mixtures (Arcaro et al, 1998). Likewise, the estrogenic activities of these two OH-PCBs were additive when tested as equimolar mixture in several systems (MCF-7 cells, MDA-MB-231 human breast-cancer cells, mouse uterus) at high and low levels of estrogen-receptor expression, confirming the lack of a synergistic effect .…”
Section: In-vitro Assaysmentioning
confidence: 57%
“…Although the individual OH-PCBs were estrogenic in both assays, there was no synergy when they were combined at various concentrations as equimolar mixtures (Arcaro et al, 1998). Likewise, the estrogenic activities of these two OH-PCBs were additive when tested as equimolar mixture in several systems (MCF-7 cells, MDA-MB-231 human breast-cancer cells, mouse uterus) at high and low levels of estrogen-receptor expression, confirming the lack of a synergistic effect .…”
Section: In-vitro Assaysmentioning
confidence: 57%
“…Figure 11 shows Log molarity of E2 -8 Figure 11. The estrogenic effects of three concentrations of 2,4,6-trichloro-4'-biphenylol alone and together with dose-response curves of E2 in the MCF-7 cell focus assay, as described by Arcaro et al (42). The data show no synergistic effect when the biphenylol at various concentrations was added together with E2.…”
Section: Polychioinated Biphenyls As Chemical Mixuementioning
confidence: 79%
“…On the basis of this assumption, some have concluded that the PCBs that cannot assume a coplanar configuration are nontoxic (31), but this has now been proven incorrect. Results from our laboratories and those of a number of other researchers (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) (32) showed that congeners with two or more ortho chlorines inhibit the enzyme tyrosine hydroxylase, which is the rate-limiting enzyme for the synthesis of the neurotransmitter dopamine. Kodavanti et al (33) and Carpenter et al (34) showed that orthosubstituted, but not coplanar, congeners kill cerebellar granule cells by a mechanism that probably involves disruption of calcium homeostasis.…”
Section: Polychioinated Biphenyls As Chemical Mixuementioning
confidence: 99%
“…1) also contain EDC activity. 15,16) A few of the numerous QSAR models available to describe EDC activity are discussed below to illustrate the breadth of available methodologies and applications.…”
Section: Applications Of Structure-activity Relationships To Endocrinmentioning
confidence: 99%